2017
DOI: 10.1002/nau.23088
|View full text |Cite
|
Sign up to set email alerts
|

How does lower urinary tract dysfunction (LUTD) affect sexual function in men and women? ICI‐RS 2015—Part 2

Abstract: Neurovascular and hormonal factors, but also indirect effects may link LUTD to SD in both sexes, but the evidence is not robust and the mechanisms unclear. There is a need for defining the terminology and standardizing outcomes assessed in clinical trials. The multifactorial nature of SF in both sexes makes trial design challenging and "real world" studies may prove more beneficial for patients' outcomes and clinicians' understanding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…3 After surgical or conservative restoration of continence, improvement of SF was observed, and the goal of improving sexuality and body image was an independent predictor of better SF. 4 However, there are conflicting reports after POP surgery, where sexual satisfaction remains unchanged 3,5 or improved. 6 In older women, marital status remains the strongest predictor of sexual activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 After surgical or conservative restoration of continence, improvement of SF was observed, and the goal of improving sexuality and body image was an independent predictor of better SF. 4 However, there are conflicting reports after POP surgery, where sexual satisfaction remains unchanged 3,5 or improved. 6 In older women, marital status remains the strongest predictor of sexual activity.…”
Section: Introductionmentioning
confidence: 99%
“…In a group of sexually active patients with POP stage III or IV, one third believed that POP affected their ability to have sexual relations . After surgical or conservative restoration of continence, improvement of SF was observed, and the goal of improving sexuality and body image was an independent predictor of better SF . However, there are conflicting reports after POP surgery, where sexual satisfaction remains unchanged or improved …”
Section: Introductionmentioning
confidence: 99%
“…Our study revealed that LUTS increased the likelihood of developing ED by 2.3 times, even when adjusting for age, gender, education, or comorbidities. This relationship has been extensively investigated, providing evidence for the causal relationship between LUTS and ED [ 68 ]. The prevalence of moderate-to-severe ED was 63% within our population, rising to 84% in patients experiencing at least mild ED.…”
Section: Discussionmentioning
confidence: 99%
“…Summary: It has been reported that approximately half of women with LUTS present sexual dysfunction, and that LUTS are an independent risk factor for female sexual dysfunction. [12][13][14][15] There is a higher rate of sexual dysfunction in OAB with urinary incontinence (OAB-wet) than in OAB-dry, and sexual dysfunction improves with treatment for OAB. [16][17][18][19] Stress urinary incontinence is strongly involved in urinary incontinence during sexual intercourse, with reduced urethral resistance contributing the most.…”
Section: Selected Cqsmentioning
confidence: 99%